2009
DOI: 10.1242/jeb.030411
|View full text |Cite
|
Sign up to set email alerts
|

Effects of crowding on ornithine–urea cycle enzyme mRNA expression and activity in gulf toadfish (Opsanus beta)

Abstract: SUMMARYThe gulf toadfish (Opsanus beta) is a facultatively ureotelic fish that excretes primarily urea under conditions of crowding or confinement. To examine the relationship between ammonia production, urea production and the ornithine-urea cycle (O-UC) enzyme activity and mRNA expression, we subjected toadfish to two-day and seven-day crowding regimes. Plasma cortisol levels were measured and liver tissue was assayed for ammonia and urea concentrations. Liver glutamine synthetase (GS), carbamoyl phosphate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 43 publications
2
10
0
Order By: Relevance
“…This pro-65% ‫ע‬ 8.5% portion is considerably lower that the ∼90% ureotely reported above and in laboratory trials with individuals stressed by confinement (Wood et al 2003), but it was similar to the proportion observed in toadfish in their natural habitat in Florida Bay in that ∼50% of waste N appeared to be excreted as urea N ( Barimo et al 2004Barimo et al , 2007. Given the much lower levels of cortisol (and presumably stress) in mesocosm-held toadfish at low densities (Laberge et al 2009;McDonald et al 2009), it is tempting to speculate that low cortisol levels are necessary to allow the 1 : 1 excretion ratio of ammonia N to urea N (see below). Because of the similarity of urea N to ammonia N ratios in mesocosm and field measurements, the mesocosm measurement system appears to be more reflective of toadfish in their natural habitat than either the laboratory or the outdoor flux chamber measurement systems.…”
Section: What Is the Ratio Of Ammonia : Urea Excreted By Toadfish In supporting
confidence: 56%
See 2 more Smart Citations
“…This pro-65% ‫ע‬ 8.5% portion is considerably lower that the ∼90% ureotely reported above and in laboratory trials with individuals stressed by confinement (Wood et al 2003), but it was similar to the proportion observed in toadfish in their natural habitat in Florida Bay in that ∼50% of waste N appeared to be excreted as urea N ( Barimo et al 2004Barimo et al , 2007. Given the much lower levels of cortisol (and presumably stress) in mesocosm-held toadfish at low densities (Laberge et al 2009;McDonald et al 2009), it is tempting to speculate that low cortisol levels are necessary to allow the 1 : 1 excretion ratio of ammonia N to urea N (see below). Because of the similarity of urea N to ammonia N ratios in mesocosm and field measurements, the mesocosm measurement system appears to be more reflective of toadfish in their natural habitat than either the laboratory or the outdoor flux chamber measurement systems.…”
Section: What Is the Ratio Of Ammonia : Urea Excreted By Toadfish In supporting
confidence: 56%
“…Overall, the plasma cortisol measurements in the Series IV mesocosm experiments were higher than those observed in freshly collected toadfish from the field and at the lower densities typical of mesocosm experiments similar to those in Series III (Laberge et al 2009;McDonald et al 2009), but they were at the lower end of the range for cannulated laboratory fish in confined conditions . While plasma cortisol levels should not be viewed as a simple proxy for stress levels, these values indicate that there is at least some level of stress-related disturbance at the densities used in Series IV of this study, even in toadfish that, while fasted, are well nourished and excreting nitrogen at a relatively high rate.…”
Section: Are There Diurnal Patterns In Levels Of Plasma Effector Molementioning
confidence: 55%
See 1 more Smart Citation
“…Similar association was described for liver LDH-B mRNA and the protein it codes in gulf killifish exposed to~13.5% air saturation for 4-48 h (Crawford et al 1999;Everett et al 2012) and considered to be generally true for many other metabolic genes ). This good correlation may be best explained by transcriptional regulation where mRNA is a good predictor of specific enzyme activity (Haas et al 2005) for a number of reasons including mRNA stability that is similar to the in vivo protein half-life (Laberge et al 2009). The second pattern implies poor association, where increases in mRNA levels were recorded with no equivalent increase in enzyme activities, as in the case of liver PK and muscle LDH after short-term exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Glucocorticoids, specifically the stress hormone, cortisol, have been shown to play a key role in the regulation of this pulsatile process (Wood et al, ; McDonald et al, ; Rodela et al, ). While the chronic elevation of cortisol in response to a stressor initiates the production of urea (Walsh et al, ; Hopkins et al, ; Laberge et al, ) as well as an upregulation in tUT mRNA expression (McDonald et al, ) and initial membrane recruitment (Rodela et al, ), cortisol also inhibits pulsatile urea excretion as the activation or insertion of tUT into the gill membrane appears to only occur when cortisol levels are periodically reduced (Wood et al, ; McDonald et al, ; Rodela et al, ). The drop in cortisol alone does not trigger the urea pulse since a natural drop in cortisol can be observed without a corresponding pulse occurring (Wood et al, ).…”
mentioning
confidence: 99%